An approach to understanding the specific subsidies recevied by rural civic organizations: A case of a settlement in Szabolcs-Szatmár-Bereg County - Szabados, György; Bácsné Bába, Éva; Kulcsár, Gergely; Zulfiqar, Sehar (Applied Studies in Agribusiness and Commerce, 2016)
Nowadays the sport related civic organizations form a special segment within the civic sector. In particular, the current situation of these organizations – who are operating in rural settlements – should be considered as special. In rural settlements the local sport related civic organizations by all means could be justified to make a difference on the basis of an essential aspect, that how they secure the funds from the external sources, and because of certain aspects it is closely related with the local politics. The purpose of our study was to investigate through the example of a small rural town in Hungary, that what kind of subsidies can the locally registered sport related civic organizations can get by focusing on the local football club’s results and the subsidies which were granted to the club between 2007 and 2015. We were also curious about, that is there any possible connection between the club’s performance and these certified subsidies. JEL CODE: L31, Z20, H71, D72